2011
DOI: 10.1080/14616734.2011.553991
|View full text |Cite
|
Sign up to set email alerts
|

Early maternal separation, nightmares, and bad dreams: Results from the Hungarostudy Epidemiological Panel

Abstract: Early maternal separation is a particularly stressful experience. Current models of nightmare production emphasize negative emotionality as having a central role in determining dream affect. Our aim is to test the hypothesis that persons who experienced early maternal separation (before one year of age and lasting at least one month) report more frequent nightmare experiences and bad dreams as adults. In the frame of the Hungarostudy Epidemiological Panel, 5020 subjects were interviewed. Significant associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 71 publications
3
23
0
1
Order By: Relevance
“…A study of very early adversity (62) in a nationally representative sample of 5,020 Hungarian adults demonstrated an association between retrospectively reported maternal separation for at least a month in the first year of life and currently recalling frequent nightmares. The effect was independent of age, gender, and education, but not depression.…”
Section: The Ravages Of Early Adversitymentioning
confidence: 99%
“…A study of very early adversity (62) in a nationally representative sample of 5,020 Hungarian adults demonstrated an association between retrospectively reported maternal separation for at least a month in the first year of life and currently recalling frequent nightmares. The effect was independent of age, gender, and education, but not depression.…”
Section: The Ravages Of Early Adversitymentioning
confidence: 99%
“…Nightmares and bad dreams are also frequent in other populations with dissociative symptoms (Agargün, Kara, Ozer, Selvi, Kiran & Kiran, et al ., ; Agargün, Kara, Ozer, Selvi, Kiran & Ozer,), suicidal behavior (Agargün et al ., ; Agargün, Besiroglu, Cilli et al ., ; Sjöström, Waern & Hetta, ; Tanskanen, Tuomilehto, Viinamäki, Vartiainen, Lehtonen & Puska, ) – two features characteristic in BPD. Moreover, nightmare prevalence and disturbed dreaming were associated to adverse childhood experiences such as early‐life maltreatment (Schäfer & Bader, ) and early maternal separation (Csóka, Simor, Szabó, Kopp & Bódizs, ), events having long‐term impact on the development of BPD (Crawford, Cohen, Chen, Anglin & Ehrensaft, ; Steele & Siever, ). Accordingly Semiz and colleagues () found that heightened dream anxiety as well as impaired subjective sleep quality in BPD patients were related to higher rates of early traumatic experiences.…”
Section: Disturbed Dreaming In Bpdmentioning
confidence: 99%
“…They are more common in women and are associated with an increase in nocturnal awakenings, sleep onset insomnia, daytime memory impairment, and anxiety due to poor nocturnal sleep 11. However, stressful experiences even occurring during childhood could influence the development of depression with sleep complaints, such as oppressive and bad dreams 12. In addition, they can be related to the use of medications, primarily those modifying the levels of neurotransmitters in the central nervous system, such as antidepressants, narcotics, or barbiturates.…”
Section: Introductionmentioning
confidence: 99%